STUDI KEPADATAN BEBAN JARINGAN DISTRIBUSI AREA DEPOK - Redaksi Tim Jurnal (Energi & Kelistrikan, 2015)
Increasing electricity demand in various sectors of the consumer in line with the development in the area indicates that the area is growing. In order to overcome these problems and to develop the electricity network is economical but efficient. Analysis loading unit network settings on a power system is very important. One method given in this paper is to approach the analysis of technical data network. Optimal use of the network is required in order to obtain concessions that benefit both economically and technically. So the network is not overly burdened and no less in the assignment. Of technical data that is in the field will get the value that indicates the magnitude of the density of the network load. And what will be required of network development.